The Institutionalization of Service-Learning at the Independent Colleges and Universities of the Gulf Coast Region. Issue 4 (8th August 2017) - Lewing, Morgan; Shehane, Melissa
ABSTRACT: Service-learning is a high-impact educational practice that benefits the community, the university, and students (Jacoby, 2015). It also represents an educational practice that specifically supports the integration of Christian thought and action within Christian institutions (Schaffer, 2004). The purpose of the study was to determine the level of service-learning institutionalization within the faith-based, faith-affiliated, and secular institutions of the Gulf Coast Region of the United States. Utilizing an electronic version of Furco's (2009 ) Self-Assessment Rubric for the Institutionalization of Service-Learning in Higher Education, chief academic officers at independent colleges and universities of the Gulf Coast region provided their respective institution's current stage of development on the institutionalization continuum. The majority of administrators reported scores indicative of development at the midpoint of the continuum, the Quality Building Stage. The presence of a university philosophy and mission was the most developed dimension, and community partner involvement was the least developed. This study provides data-driven, researched-based recommendations regarding the institutionalization of service-learning for Christian colleges and universities.